Industrial training: Pelapis Maju Sdn. Bhd. / Nur Ain Marsitah Razlan - Razlan, Nur Ain Marsitah (Bachelor of Science (HONS) Record Management, 2015)
All bachelor degree students are required to undergo industrial training for five month as part of their curriculum to complete their 2 year course for the Bachelor of Science (Hons) Record Management. The attachment will be during the 7th semester of their study. During five month period of training, student will be supervised and monitored their training by two supervisors that's from the faculty and one from the organization. For my industrial training, i did at Pelapis Maju Sdn Bhd situated at Malacca. It is a waste management company; Pelapis Maju Sdn Bhd was established in year 1998. It is a 100% native businessman under the Ministry of Finance as a company that runs the service area cleaning, picking up trash, contract workers, beautification of the area, supply and transportation. I was assigned to the Administration/Human Resource Department which my supervisor is Mr Mohd Syafiq bin Mohd Nor, and for this five month, I was assigned with various task, lots of new thing that can be gain from the Pelapis Maju Sdn Bhd. I learn lots of thing from my industrial training such as handling various records of the company. It was exciting in undertaking the task that has been given to me because we can implement the skill and experience at other places after finish with the industrial training. Some of the processes were repeated daily.